Asia rising : - Rohwer, Jim (Butterworth-Heinemann Asia, 1995)
The extraordinary economic success of East and Southeast Asia over the last forty years, and the likelihood that this success will continue during the next twenty-five years and expand to India, is one of the great events of the second half of the twentieth century. In one of the year's most provocative business books, Jim Rohwer argues that the wealth generated by Asia's resurrection will create tides of business and financial opportunities for Western companies and their workers.